More than words: Potential roles for independent fiscal institutions (IFIs) in green budgeting - Cameron, Scott (OECD Publishing, 2022)
Budgetary frameworks and instruments are increasingly being used to support and accelerate progress towards climate and environmental goals. This paper provides an overview of how OECD countries are implementing green budgeting and potential roles for independent fiscal institutions (IFIs) in monitoring these initiatives or in providing climate-related analysis as part of their existing mandates. It concludes with some key questions for the path ahead
Keywords: Finance and Investment; Governance; Economics